Geographic Information System EVALUATION OF ENVIRONMENTAL QUALITY OF SETTLEMENTS IN MANDALAJATI DISTRICT, BANDUNG CITY USING REMOTE SENSING AND GEOGRAPHIC INFORMATION SYSTEM - Nugraha, Muhamad Aditya (JURNAL GEOGRAFI, 2025)
ABSTRACT EVALUATION OF ENVIRONMENTAL QUALITY OF SETTLEMENTS IN MANDALAJATI DISTRICT, BANDUNG CITY USING REMOTE SENSING AND GEOGRAPHIC INFORMATION SYSTEM Muhamad Aditya Nugraha The quality of the residential environment is a combination of the conditions of a residential environment including aspects of house conditions, sanitation and basic residential infrastructure. Rapid population growth accompanied by the decreasing availability of land for settlements has raised concerns regarding the quality of the residential environment. This study aims to evaluate the level of quality of the residential environment in Mandalajati District, as well as to test the accuracy of the results of Pleiades image processing and Geographic Information Systems (GIS) in assessing the quality of the residential environment. The research method used involves the interpretation of remote sensing imagery with a scoring and overlay approach. The results of this study indicate that the parameters that determine the quality of the residential environment based on Pleiades imagery include residential density, building layout, width of residential entrance roads, number of protective trees, location of settlements, and quality of building roofs. Analysis of the distribution of the level of environmental quality of settlements in Mandalajati District shows that 45% of the total area is classified as poor, 28% is in moderate, and 27% is in good. The accuracy of image processing and mapping is tested using a confusion matrix, with the accuracy reaching 92%. This study provides an important contribution to understanding the relationship between population density and the quality of the residential environment, and shows the effectiveness of using remote sensing and GIS technology in monitoring the quality of the residential environment. Keywords: Residential Environmental Quality, Remote Sensing, Geographic Information System.